Magnitude and risk factors for postpartum symptoms: A literature review - Norhayati, M.N.; Nik Hazlina, N.H.; Asrenee, A.R.; Wan Emilin, W.M.A. (Journal of affective disorders, 2015)
The prevalence of postpartum depression worldwide varies from 0.5% to 60.8% in the first 12 months postpartum using self-reported questionnaire. This review aims to update the current magnitude of postpartum depression based on self-reported questionnaire and clinical interview and explore its associated factors in developed and developing countries. A literature search conducted between 2005 and 2014 identified 203 studies, of which 191 used self-reported questionnaire in 42 countries and 21 used structured clinical interview in 15 countries. Nine studies used a combination of self-reported questionnaire and clinical interview. The prevalence of postpartum depression varies from 1.9% to 82.1% in developing countries and from 5.2% to 74.0% in developed countries using self-reported questionnaire. Structured clinical interview shows a much lower prevalence range from 0.1% in Finland to 26.3% in India. Antenatal depression and anxiety, previous psychiatric illness, poor marital relationship, stressful life events, negative attitude towards pregnancy, and lack of social support are significant contributors to postpartum depression. All studies are included irrespective of the methodological quality, such as small sample size and their inclusion could affect the generalizability of the results. The current prevalence of postpartum depression is much higher than that previously reported, and similar risk factors are documented. A culturally sensitive cut-off score with adequate psychometric properties of the screening instruments should be available. In future studies, examining the physical, biological, and cultural factors in qualitative studies and in those with adequate methodological qualities is recommended.